Analisis Potensi Kesiapan Petani Padi Sawah untuk Bisa Menerima Rencana Program Pengembangan Usaha Sutera Kerakyatan di Kawasan Irigasi Teknis Kecamatan Belitang - Iman sulaiman; Maryadi; Mirza Antoni (Jurnal Bakti Agribisnis, 2017)
The purposes of this research were to : (1) Measure the potential yard, free time, farmer’s income and potential of readiness farmers in establishing PUSK programme at the area technical irrigation channels, (2) Analyze opportunity of farmer’s decision to be clasified in accordance with social economic potenttially in PUSK programme. The research was conducted in Belitang Sub District OKU Timur Regency. This research was done on April until August 2015 by survey and disproporsionated stratified random sampling method, and also took 63 samples. The research found that farmers have a yard > 200 m2 were 93,65% and the free time of work were 169.045 HOK/year. While, the average farmer’s income were Rp.19.378.276./ha/year. The farmers might be potential and comitmen in PUSK proggram were 74,60%. There were correlation of the readness farmers with perseption farmers as supporting PUSK proggram α = 5 %, so PUSK proggram PUSK can to buid.